2019
DOI: 10.9734/jsrr/2019/v23i330124
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Alarming Microbial Pathogens over Refuse Dump Sites and Its ‘Harmful Distance’ in Port Harcourt, Southern Nigeria

Abstract: Aim: Microbial air quality over illegal refuse dump sites in Port Harcourt, Nigeria, was conducted to assess the aero-microbial contaminant of dumpsite to the closest neighbourhood and the harmful distance. Place and Duration of Study: The dump sites were located at oil mill market (Latitude 4.8578 N4°51'28.06344'' Longitude 7.06653 E7°3'59.50152'') and Iloabuchi Timber market (longitude N4.790191, latitude E6.988416) all in Port Harcourt, South South Nigeria. The samplings were carried out between June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 6 publications
2
6
0
Order By: Relevance
“…Based on Figures 1 and 2, there is an indication of seasonal influence in the distribution of fungi aerosols around the market The findings of this study agree with previous report that indicates that fungi density in air is higher in dry season compared to wet season [4,7]. The wet season (characterized by low temperature and high relative humidity) enhances sporulation and subsequent release in the dry season (that is characterized by higher temperature and low relative humidity).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Based on Figures 1 and 2, there is an indication of seasonal influence in the distribution of fungi aerosols around the market The findings of this study agree with previous report that indicates that fungi density in air is higher in dry season compared to wet season [4,7]. The wet season (characterized by low temperature and high relative humidity) enhances sporulation and subsequent release in the dry season (that is characterized by higher temperature and low relative humidity).…”
Section: Discussionsupporting
confidence: 89%
“…Based on Figures 3,4,5,6, the isolates recorded in this study have been widely reported in different environments including dumpsite [4,6,7], University environment (Cafiteria, Toilets, Laboratory and laboratory preparatory rooms) [2], health centres [9,17]. Studies have shown that Aspergillus species has the highest frequency in the ambient environment [2,6,7,17]. This corresponds with findings of this study.…”
Section: Discussionsupporting
confidence: 85%
“…The sedimentation method previously described by Nrior and Dumbor [7], was adopted for this study. Triplicate samples of petri dish containing sterile Potatoes dextrose agar was exposed to the air environment at 1m height for 10 minutes.…”
Section: Collection Of Samplesmentioning
confidence: 99%
“…The agar plates exposed to the market environment for 10 minutes were incubated at 30ºC for 5 days [4]. The colonies were counted and expressed as colony forming units (CFU)/min-m 2 as described by Nrior and Dumbor [7], and the fungi was sub-cultured into pure culture.…”
Section: Examination Of the Fungi Countsmentioning
confidence: 99%
See 1 more Smart Citation